2013
DOI: 10.1186/1745-6215-14-24
|View full text |Cite
|
Sign up to set email alerts
|

Rotterdam Aphasia Therapy Study (RATS) – 3: “The efficacy of intensive cognitive-linguistic therapy in the acute stage of aphasia”; design of a randomised controlled trial

Abstract: BackgroundAphasia is a severely disabling condition occurring in 20 to 25% of stroke patients. Most patients with aphasia due to stroke receive speech and language therapy. Methodologically sound randomised controlled trials investigating the effect of specific interventions for patients with aphasia following stroke are scarce. The currently available evidence suggests that intensive speech and language therapy is beneficial for restoration of communication, but the optimal timing of treatment is as yet uncle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…In summary the type, duration, intensity and earlier commencement of aphasia therapy may be considered a determinant factor for better recovery (David et al 1982). The 'Rotterdam Aphasia Therapy Study-3' when concluded may give a better insight into the role of early-intensive cognitive therapy compared to regular language therapy (Nouwens et al 2013). [For summary see Table 3] …”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In summary the type, duration, intensity and earlier commencement of aphasia therapy may be considered a determinant factor for better recovery (David et al 1982). The 'Rotterdam Aphasia Therapy Study-3' when concluded may give a better insight into the role of early-intensive cognitive therapy compared to regular language therapy (Nouwens et al 2013). [For summary see Table 3] …”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Indeed, there is limited evidence on what speech and language therapy programs lead to gains in quality of life. Encouragingly, currently ongoing trials include either generic (EuroQoL) [37] quality of life measures [38] or stroke- and aphasia-specific measures (SAQOL-39g) [39,40], so this evidence will soon begin to emerge. Additionally, other interventions have specifically targeted psychosocial well-being in people with aphasia [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…For external validation of the SPEAK-model we used data from the Rotterdam Aphasia Therapy Study (RATS) – 3, a randomized controlled trial (RCT) studying the efficacy of early initiated intensive cognitive-linguistic treatment for aphasia due to stroke, conducted between 2012 and 2014 [ 21 , 22 ]. RATS-3 was approved by an independent medical ethical review board.…”
Section: Methodsmentioning
confidence: 99%